Comparing the Effects of Immersed Versus Land-Based High-Intensity Interval Cycling on Energy Intake, Appetite Sensations and Perceived Exertion Among Healthy Men. Issue 4 (August 2021) - Metz, Lore; Isacco, Laurie; Miguet, Maud; Genin, Pauline; Thivel, David; Duclos, Martine
Immersed exercise has been shown to induce higher energy expenditure and no difference or increase in food intake compared with similar exercise on land. In this study, we compared the effects of acute high-intensity cycling performed on land versus when immersed on subsequent energy intake (EI), appetite sensations and perceived exertion (RPE) in healthy men. Ten participants in a postprandial condition completed three experimental visits in a randomized order: a control condition (CONT); a high-intensity interval cycling exercise performed on land (HIIE-L) and the same exercise while immersed in water (HIIE-A) with a similar targeted heart rate. We observed no difference in energy and macronutrient intake and in area under the curve (AUC) for appetite sensations between sessions. The RPE at the end of HIIE-L was negatively correlated with EI (r=–0.67; p  < 0.05), AUC for hunger (r=–0.86, p  < 0.01), desire to eat (r=–0.78, p  < 0.05) and prospective food consumption (r=–0.86, p  < 0.01). Conversely, the RPE at the end of HIIE-L was positively correlated with AUC for fullness (r = 0.76, p  < 0.05). No such correlations were observed for HIIE-A. The present study was the first to observe that immersion did not influence EI after HIIE cycling, but immersion blunted the relationship between session RPE and subsequent energy intake and appetite sensations relative to HIIE on land.